2008
DOI: 10.1200/jco.2008.26.15_suppl.18017
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual well-being in long-term survivors with chronic graft versus host disease after hematopoietic stem cell transplant

Abstract: Background Spiritual well-being (Sp-WB) is a resource that supports adaptation and resilience, strengthening quality of life (QOL) in patients with cancer or other chronic illnesses. However, the relationship between Sp-WB and QOL in patients with chronic GVHD (cGVHD) remains unexamined. Methods 52 participants completed the Functional Assessment of Chronic Illness Therapy – Spiritual Well-Being (FACIT-Sp) questionnaire as part of a multidisciplinary study of cGVHD. Results Sp-WB was generally high (Mean 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 32 publications
0
22
1
2
Order By: Relevance
“…Studies also suggest that increased physical burden of disease was associated with lower SWB (Lo, Burman, et al, 2011;Lo, Zimmermann, Gagliese, Li, & Rodin, 2011;Zimmermann et al, 2014). Finally, previous studies have identified a relationship between depression and worse spirituality and/or SWB (Costanzo, Ryff, & Singer, 2009;Gonzalez et al, 2014;Johnson et al, 2011) and low emotional and physical well-being and decreased spirituality (Harris et al, 2010).…”
Section: Funding Informationmentioning
confidence: 89%
“…Studies also suggest that increased physical burden of disease was associated with lower SWB (Lo, Burman, et al, 2011;Lo, Zimmermann, Gagliese, Li, & Rodin, 2011;Zimmermann et al, 2014). Finally, previous studies have identified a relationship between depression and worse spirituality and/or SWB (Costanzo, Ryff, & Singer, 2009;Gonzalez et al, 2014;Johnson et al, 2011) and low emotional and physical well-being and decreased spirituality (Harris et al, 2010).…”
Section: Funding Informationmentioning
confidence: 89%
“…Activities such as communing with nature, art, community, meditation, contemplation, and religious services can resonate with one’s spirituality, which is an important aspect of making meaning in one’s life (Manning 2012). Spirituality is a resource that supports adaptation and resilience to improve quality of life in patients with cancer or other chronic illnesses (Harris et al 2010). Dyer (2011) suggests that the diagnosis of cancer can precipitate spiritual reflection when faced with the possibility of death.…”
Section: Spirituality and Religiosity In Cancer Copingmentioning
confidence: 99%
“…While many factors influence an individual’s physical, emotional and mental health, spiritual well-being has been identified as an important resource in managing the challenges of intensive cancer treatment, including HSCT. (Canada et al, 2013; Farsi, Dehghan Nayeri, & Negarandeh, 2010; Gonzalez et al, 2014; Harris et al, 2010; King, Fitchett, & Berry, 2013; Ragsdale, Hegner, Mueller, & Davies, 2014; Yanez et al, 2009). While spiritual well-being may incorporate an existential relationship with a higher power that strengthens one’s beliefs, values and life purpose, (Anandarajah & Hight, 2001; Hoffert, Henshaw, & Mvududu, 2007), spiritual well-being is distinct from religiosity, defined as a formalized belief system experienced through ritual behaviors and shared religious beliefs usually practiced in community with other individuals (Hodge, 2005; Musgrave, Allen, & Allen, 2002; Taylor, 2001).…”
Section: Introductionmentioning
confidence: 99%